Construction of Open Defecation Behavior in River Bank Communities (Analysis Study of Community Social Behavior) - Niken Nagita; Fahrunnisa; Ery Sofiatry (Cigarskruie: Journal of Educational and Islamic Research, 2024)
This research aims to examine further the open defecation behavior carried out by people who live on riverbanks. The subjects of this research are the people of the Pekat sub-district who live around the river banks, especially around RT 001 RW 08. In this context, the research uses a descriptive qualitative approach with observation, interviews, and documentation methods. To analyze this research, Social Construction theory is divided into three parts, namely externalization, objectivation and internalization. The research results show that the behavior of open defecation in rivers is considered normal by some people because of primary socialization from people closest to them and hereditary habits. Factors causing this negative action include low knowledge, the impact of natural disasters, and lower middle economic conditions so that rivers are used for various purposes. In conclusion, this behavior originates from the experience and knowledge of society that has been obtained long ago and continues to be confirmed today. There is no new experience or knowledge regarding proper defecation behavior. So until now, people still defecate in the river.